2023
DOI: 10.1038/s41598-023-45297-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: predictive value of organoids in colorectal cancer

B. Cristoffer Sakshaug,
Evelina Folkesson,
Tonje Husby Haukaas
et al.

Abstract: While chemotherapy alone or in combination with radiotherapy and surgery are important modalities in the treatment of colorectal cancer, their widespread use is not paired with an abundance of diagnostic tools to match individual patients with the most effective standard-of-care chemo- or radiotherapy regimens. Patient-derived organoids are tumour-derived structures that have been shown to retain certain aspects of the tissue of origin. We present here a systematic review of studies that have tested the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Thirdly, in line with previous research showing that bias caused by the proliferation rate of PDOs can be avoided by using GR metrics for organoid response analysis [ 32 ], we confirm that using GR metrics improved the correlation with patient response. Despite good correlations of PDO and clinical response in studies employing both percentage viability and GR metrics [ 6 , 7 ], we found that GR metrics showed better correlation with patient response than percentage viability metrics. Previous studies used DRC parameters AUC, IC 50 , GR 50 or GR max to evaluate organoid response [ 14 16 , 23 ].…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…Thirdly, in line with previous research showing that bias caused by the proliferation rate of PDOs can be avoided by using GR metrics for organoid response analysis [ 32 ], we confirm that using GR metrics improved the correlation with patient response. Despite good correlations of PDO and clinical response in studies employing both percentage viability and GR metrics [ 6 , 7 ], we found that GR metrics showed better correlation with patient response than percentage viability metrics. Previous studies used DRC parameters AUC, IC 50 , GR 50 or GR max to evaluate organoid response [ 14 16 , 23 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Regarding the correlation of PDO response with clinical response, our findings are in line with previous results. In a recent systematic review the overall positive predictive value for organoid informed treatment for CRC is 68% and the negative predictive value is 78% for standard of care chemotherapy, targeted therapy and radiotherapy [ 6 ]. In literature, consistent results are seen for 5-FU and irinotecan-based treatment, showing good correlations of the AUC with both RECIST response and PFS in several, relatively small, studies which align with our results [ 6 , 7 , 14 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organoids are used to model the various stages of cancer progression from initiation to metastasis [26,27], and to study drivers of colorectal carcinogenesis including chronic inflammation [28]. CRC organoids have been shown to be highly predictive of patient response to anticancer therapies [29], and can be utilized to identify new CRC biomarkers and develop novel treatment strategies for CRC subtypes with poor prognosis [30,31]. Organoid technology has enabled the in vitro study of diverse CRC subtypes and different disease stages; and has the potential to revolutionize drug development and patient treatment.…”
Section: Organoid Models For Studying Colorectal Cancermentioning
confidence: 99%